Records of lichen species from genus Acarospora, new for Serbia, Southwest Balkan Peninsula - Aleksić Gordana; Vasić Predrag; Jakšić Tatjana (Bulletin of Natural Sciences Research, 2023)
The lichens: Acarospora impressula, A. nitrophila, A. nodulosa, A. schleicheri, A. sinopica, A. smaragdula and A. umbillicata, collected in North Kosovo are reported as a new species to Serbia, following a recent lichenological survey. Location, herbarium deposits and substrates are given, together with notes on distribution of the reported taxa.